The Cost and Funding of a Partial Social Benefit in Spain. Issue 1 (March 2016) - Peña‐Miguel, Noemí; De La Peña, J. Iñaki
Abstract: In a situation of economic crisis, it is common to find high unemployment and stringent requirements for access to social assistance for those who are most in need. International organizations such as the World Bank, the International Labour Organization, and the European Parliament have proposed designing a minimum benefit payment. We have calculated the estimated cost of a partial social benefit in order to cover basic goods for citizens who do not work. We propose a financial model, suitable for ensuring the economic, financial, and social sustainability of this measure. This model could also be extrapolated to other countries.